1992
DOI: 10.1002/ccd.1810270411
|View full text |Cite
|
Sign up to set email alerts
|

Collagen application for sealing of arterial puncture sites in comparison to pressure dressing: A randomized trial

Abstract: One hundred patients undergoing routine diagnostic or interventional catheterization were randomly assigned to receive either percutaneously applied collagen (group A; n = 50) or conventional pressure dressing (group B; n = 50) for sealing of the femoral artery. Clinical variables were comparable in both groups. The heparin dose was 100 IU/kg in 30 patients and 200 IU/kg in 20 patients of either group. The average compression time was 4.3 min in group A and 42.3 min in group B (p < .001). Bleeding was not obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 14 publications
(2 reference statements)
3
41
0
1
Order By: Relevance
“…It was originally studied in a cohort of 100 patients undergoing diagnostic or interventional catheterization procedures and randomized to the device or to conventional pressure dressing. 50 Use of the Vasoseal resulted in a shorter compression time (4 versus 42 minutes, PϽ0.001) and faster ambulation (6 versus 22 hours, PϽ0.001) and demonstrated a trend toward a reduction in bleeding rates. 50 -52 The efficacy of the Vasoseal was subsequently confirmed in other randomized studies, 53,54 although other trials showed small increases in access-site complications or failed to demonstrate superiority over mechanical compression during PCI.…”
Section: Collagen-mediated Devicesmentioning
confidence: 98%
“…It was originally studied in a cohort of 100 patients undergoing diagnostic or interventional catheterization procedures and randomized to the device or to conventional pressure dressing. 50 Use of the Vasoseal resulted in a shorter compression time (4 versus 42 minutes, PϽ0.001) and faster ambulation (6 versus 22 hours, PϽ0.001) and demonstrated a trend toward a reduction in bleeding rates. 50 -52 The efficacy of the Vasoseal was subsequently confirmed in other randomized studies, 53,54 although other trials showed small increases in access-site complications or failed to demonstrate superiority over mechanical compression during PCI.…”
Section: Collagen-mediated Devicesmentioning
confidence: 98%
“…The size of hematoma/ecchymosis was measured before ambulation by planimetry and expressed in cm 2 .…”
Section: Definition Of Bleeding and Peripheral Complicationsmentioning
confidence: 99%
“…With the development of new sealing devices for closing femoral arterial puncture sites, immediate sheath pulling in anticoagulated patients with a low risk of bleeding complications became reality [1][2][3][4][5][6][7][8]. Whereas the administration of the vascular hemostatic device (VHD) on the surface of the arterial puncture site [9] as well as the application of a suture-mediated closure device [10] are straightforward (using deployment techniques with standardized application protocols), the use of the hemostatic puncture closing device (HPCD) [11] allows several possibilities regarding its deployment time (DT): the recommended DT of 30 minutes [11] leads to a prolonged stay in the catheterization laboratory facilities, slowing down the transfer of the patients to the intermediate care unit.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen has a long history of surgical use for its hemostatic properties [16][17][18]. For this application, several different collagen plug devices have been developed and investigated in extensive laboratory and clinical trials over the past several years [19][20][21][22][23][24][25][26][27][28][29][30]. More recently, the application of fibrin sealant has been considered as a method for sealing arterial puncture sites.…”
Section: Introductionmentioning
confidence: 99%